1999
DOI: 10.1021/jp990359d
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Induced Dynamic Electron Polarization Study on the Mechanism of Exchange Interaction in Radical Ion Pairs Generated by Photoinduced Electron Transfer Reactions

Abstract: Photoinduced electron transfer reactions were studied by using the continuous wave time-resolved electron paramagnetic resonance and Fourier-transformed electron paramagnetic resonance spectroscopy in polar solvents. The chemically induced dynamic electron polarization was investigated in both singlet and triplet precursor intermolecular electron transfer systems. The signs of the exchange interaction, which are defined by the energy differences between the singlet and triplet radical ion pairs, depended on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 45 publications
7
146
2
Order By: Relevance
“…No resonance was observed for compound 1, which most likely results from the magnitude of 2 J being larger than the magnetic field that our apparatus can apply (1.2 T). Measurements of 2 J have been shown to provide a measure of the electronic coupling for charge recombination by superexchange (11)(12)(13) and have been used as a probe of electron transfer mechanism in a number of studies (2,8,9,16,18,50,51). Most importantly, the energetic splitting between the singlet and triplet states within the radical ion pair arises from an indirect exchange between the two spins made possible by their interaction with the bridge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No resonance was observed for compound 1, which most likely results from the magnitude of 2 J being larger than the magnetic field that our apparatus can apply (1.2 T). Measurements of 2 J have been shown to provide a measure of the electronic coupling for charge recombination by superexchange (11)(12)(13) and have been used as a probe of electron transfer mechanism in a number of studies (2,8,9,16,18,50,51). Most importantly, the energetic splitting between the singlet and triplet states within the radical ion pair arises from an indirect exchange between the two spins made possible by their interaction with the bridge.…”
Section: Resultsmentioning
confidence: 99%
“…The indirect electronic coupling between the electron donor and acceptor via the bridge orbitals, V DA , that is a result of superexchange (10) is the same interaction responsible for long-distance communication between the spins within a radical pair (RP), provided that the initial states are paramagnetic (11)(12)(13)(14)(15), which is true for the charge recombination process in the systems studied here. The magnetic field effect (MFE) on the yield of spin-selective RP recombination products directly reveals the magnitude of magnetic coupling between the spins of the RP and is proportional to V DA 2 (2,(16)(17)(18). The mechanistic details of the radical pair intersystem crossing mechanism (RP-ISC) and the theory behind the MFE have been researched extensively (19) and applied to many donor-acceptor systems (2,8,9,(20)(21)(22)(23)(24).…”
Section: -4 Are Only Weakly Distance Dependent After the Initial Phmentioning
confidence: 99%
“…According to these results, we concluded that the net absorption CIDEP was produced in the triplet quenching with positive J value. Radical-triplet pairs combined with covalent bond or ligand [4] and several radical ion pairs [5][6][7][8][9] have been reported exceptionally to show positive J value (for radical ion pair, J is defined as energy splitting of triplet and singlet states and the negative sign means the triplet state lies higher than the singlet), but there are so far no reports on positive J value of radical-triplet encounter pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tero and his coworkers [8,9] studied the sign of J values of various radical ion pairs and demonstrated a beautiful correlation between the sign of J and the free energy changes for the charge recombination processes. They concluded that the sign of J is controlled by the spin-selective stabilization and destabilization of ion pair states through the electronic coupling with ground and locally excited triplet states of electron donor-acceptor pair at equilibrium nuclear coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…According to the configuration interaction model, the J-coupling is induced by the singlet perturbation from the ground state configuration: 2J = -|V| 2 /E CR where E CR = G CR +  is the vertical energy gap (Fig. 5) for the charge-recombination to the ground state [16]. In the P3HT:PCBM domain interfaces, the free energy change of G CR > 1 eV in the CS state of P3HT +• PCBM -• is evidently larger at the crystalline region than the reorganization energy of , [17] supporting the positive J because of the negative E CR .…”
Section: Resultsmentioning
confidence: 99%